Tradisi Maudu Lompoa pada Masyarakat Cikoang sebagai Teater Komunal: Analisis Performativitas - Sulfiana Mansyur Putri; Ariyanti Sultan (CV. ITTC INDONESIA, 2026)
This study examines the Maudu Lompoa tradition, a religious ritual of the Cikoang community in Takalar Regency, South Sulawesi. Maudu Lompoa is a form of communal theater that represents cultural values, religiosity, and collective or communal identity through performative arts. Maudu Lompoa is a commemoration of an important day, coinciding with the birthday of the Prophet Muhammad SAW, which has been celebrated since the 17th century. This tradition is a religious ritual that also presents a social performance involving thousands of people from various backgrounds in a creative, artistic, symbolic, and collaborative process. This tradition was originally initiated by Syekh Jalaluddin, a cleric from Aceh who is believed to be a descendant of the Prophet Muhammad SAW, and has become a spiritual and cultural tradition passed down from generation to generation to this day.This study uses Judith Butler's performativity analysis and Victor Turner's social drama theory. It focuses on symbolic repetition, collective bodily participation, and ritual space, which indirectly bring out social and communal values through representation in the performance. Through participatory and narrative analysis, it was found that Maudu Lompoa is not only a form of spiritual expression, but also an arena or space for drama that strengthens solidarity and identity for the community. This study uses a qualitative approach with stages of literature study, collecting narratives, videos, photos, documents, archives and academic literature deemed relevant. The research focuses on how the Maudu Lompoa tradition in the Cikoang community represents a form of communal theater through performative elements. The results of performative analysis can reveal the meaning, identity, and social dynamics contained in the tradition of Maudu Lompoa as a performing art based on local wisdom.